The Influence of E-Commerce and Social Media on Increasing Micro-Enterprise Revenue in Banjarmasin City South Kalimantan Province - Salma Salma; Rahmi Widyanti; Basuki Basuki (SEAN Institute, 2026)
This study aims to The Influence Of E-commerce and Social Media On Increasing Micro-ENTERPRISE Revenue In Banjarmasin City South Kalimantan Province; to examine and analyze the partial effect of social media on increasing micro-business income; and to examine and analyze the simultaneous effect of e-commerce and social media on increasing micro-business income in the same region. This research employed a quantitative approach using a cluster sampling method. Data were collected through questionnaires and analyzed using multiple linear regression. The sample consisted of 100 respondents selected from 1,005 micro-entrepreneurs in Banjarmasin City, South Kalimantan Province, who use e-commerce and social media. The variables in this study were e-commerce (X1), social media (X2), and the increase in micro-business income (Y). The results of the t-test analysis showed that e-commerce has a significant effect on increasing micro-business income, with t-count > t-table (10.123 > 1.660) and a significance value of 0.001 < 0.05; therefore, H0 is rejected and H1 is accepted. Social media also has a significant effect on increasing micro-business income, with t-count > t-table (11.202 > 1.660) and a significance value of 0.001 < 0.05; therefore, H0 is rejected and H2 is accepted. Simultaneously, the F-statistic was 108.261, while the F-table value was 3.09. Since F-count > F-table, H0 is rejected and H3 is accepted. This indicates that e-commerce and social media jointly influence the increase in micro-business income in Banjarmasin City, South Kalimantan Province.